GADGET SCREEN TIME USE OF STUDENTS IN SELECTED TERTIARY INSTITUTIONS: IMPLICATIONS IN THE NEW NORMAL LEARNING - John Mark R. Asio (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
Since the advent of the pandemic, students exposed to gadgets were even more dependent than ever before. This study aims to analyze tertiary students' gadget screen time usage during the pandemic. The proponent used a descriptive research via online survey as the primary data gathering tool. The study subjected the gathered data to statistical treatment. Results show that students responded that it is "important" and they "agree" to reduce gadget screen time use. The students also "agree" on the context of expectations about screen time use, and they "often" observe a family model of screen time use in their households. Furthermore, significant differences were found in the attitude, self-efficacy, expectations, and family model of screen time use when grouped according to demographic profile. Finally, the proponent shared some implications at the end of the study.